Application of response surface methodology and box–behnken design for the optimization of mercury removal by Ulva sp - Ferreira, Nicole; Viana, Thainara; Henriques, Bruno; Tavares, Daniela S.; Jacinto, Jéssica; Colónia, João; Pinto, João; Pereira, Eduarda (Journal of hazardous materials, 2023)
Mercury (Hg) is a global and top priority contaminant, toxic at low concentrations. Although it has been progressively eliminated from processes, this metal continues to circulate in the atmosphere, soil, and water. In this work, the Response Surface Methodology (RSM) combined with a Box-Behnken Design (3 factors - 3 levels) was used to optimize key operational conditions that influence the removal and uptake of Hg by living macroalga Ulva sp. in a complex mixture containing several elements used in industry (potentially toxic elements, rare earth elements, and platinum-group elements) (initial concentration 10, 100 and 190 µg/L, salinity 15, 25 and 35, seaweed stock density 1.0, 3.0 and 5.0 g/L). Results evidenced the great capability of Ulva sp. to remove Hg, with removal efficiencies between 69 % and 97 %. 3-D surfaces showed that the most impactful variable was seaweed stock density, with higher densities leading to higher removal. Regarding the uptake, a positive correlation between initial concentration and qt values was observed. The appliance of RSM made possible to obtain optimal operating conditions for removing virtually 100 % of Hg from waters with high ionic strength, which is a pivotal step in the direction of the application of this remediation biotechnology at large scale. [Display omitted] •Response surface methodology allowed to optimize Hg removal from simulated effluent.•Seaweed stock density, salinity and initial Hg concentration were 3 key parameters.•Ulva sp. achieved > 95% removal (qt up to 377 µg/g) in 48 h.•Pseudo-first order model presented the best fitting to experimental data.•Optimized algae-based technology fosters the removal of Hg from complex systems.